Detailed Reaction Mechanisms of 4‐Pyridylboronic Acid and (N‐Methyl)‐4‐Pyridinium Boronic Acid with D‐Sorbitol in Aqueous Solution. Issue 17 (1st May 2019) - Kusuyama, Daisuke; Samukawa, Yuta; Sugaya, Tomoaki; Iwatsuki, Satoshi; Inamo, Masahiko; Takagi, Hideo D.; Ishihara, Koji
Abstract: Kinetic measurements of the reactions of (N‐methyl)‐4‐pyridinium boronic acid [(N−Me)‐4‐Py + B(OH)2 ] and 4‐pyridinium boronic acid [4‐HPy + B(OH)2 ] with D‐sorbitol in aqueous solution were performed, and the reaction mechanisms were clarified in detail. Both reactions proceeded in one step; i. e., the intermolecular rate‐determining step forming the 2, 3‐bicoordinate product was followed by the fast intramolecular step from the bicoordinate product to the 2, 3, 5‐tricoordinate product. N‐Methylation of 4‐HPy + B(OH)2 was found to dramatically reduce the reactivity of the N‐methylated‐4‐pyridinium boronate ion [(N−Me)‐4‐Py + B(OH)3 − ], although it had little effect on the reactivity of (N−Me)‐4‐Py + B(OH)2 . The reaction rates were enhanced by ion‐pair formation between the boronate ion and the protonated buffer cation. Abstract : The reactions of (N‐Methyl)‐4‐pyridinium boronic acid and 4‐pyridylboronic acid with D‐sorbitol in aqueous solution proceed through three parallel reaction paths in one step to produce the 2, 3‐bicoordinate and 2, 3, 5‐tricoordinate complexes, simultaneously, i. e., the rate‐determining intermolecular process is followed by the fast intramolecular process.